Secular Unemployment - Fleming, J. M. (Quarterly Journal of Economics, 1939)
Tendency to long-run unemployment and the factors which determine its amount, 103. — Proposed remedies: wage reduction, 109; credit expansion, 113; deficit financing, 114. — Different types of deficit financing: current consumption, 116; tax reduction and subsidies in favor of consumers' goods, 116; public investment, 118; reduced taxation or subsidies in favor of investment goods, 118; tax reduction or bounties to individuals, 120; public disbursements to property owners, 121; remission of taxation on, or subsidization of, property, 123. — Financing the deficit: the increasing public debt, 124; ways out of the dilemma, 125. — Balanced budget policy, 126. — Fancy remedies: taxation of saving, 127; taxation of money balances, 128. — Conclusion, 130.